Analisis Pengaruh Nilai Bullwhip Effect dengan Metode Single Exponential Smoothing pada PT. XYZ - Elsya Maharani; Ade Momon (Fakultas Teknik, 2023)
The Bullwhip Effect, or the significant difference in supply and demand, represents one of the issues that arise from the concept of supply chain management. Using a forecasting approach using the single exponential smoothing method, this research aims to evaluate the Bullwhip Effect's influence and lessen its incidence at PT. XYZ. The information used consists of requests and orders for MS Rack, Adapter AT, and Bracket products from January to December 2021. The Bullwhip Effect value for each product is calculated as part of data processing, while forecasting uses single exponential smoothing technique and recalculates the Bullwhip Effect value as part of the repair. According to the research results, a single exponential smoothing method with a = 0.9 results in the lowest MAD, MSE, and MAPE values and subsequently utilized to lower the bullwhip effect value. The calculation results show that the Bullwhip Effect has decreased for the three products, from 1.0008 to 1.0002 for MS Rack, from 0.9961 to 0.9957 for Adapter AT, and from 1.0035 to 1.0027 for Bracket. With these results, it is clear that demand is steady and that the Bullwhip Effect may be minimized using the single exponential smoothing approach.